2017
DOI: 10.1371/journal.pone.0181664
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two distinct web-based education tools for bedside nurses on medication administration practice for venous thromboembolism prevention: A randomized clinical trial

Abstract: BackgroundVenous thromboembolism (VTE) is a common cause of preventable harm in hospitalized patients. While numerous successful interventions have been implemented to improve prescription of VTE prophylaxis, a substantial proportion of doses of prescribed preventive medications are not administered to hospitalized patients. The purpose of this trial was to evaluate the effectiveness of nurse education on medication administration practice.MethodsThis was a double-blinded, cluster randomized trial in 21 medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
0
44
0
2
Order By: Relevance
“…Cluster randomized trials might randomize at the floor, unit, clinic, or hospital level. For example, a cluster randomized trial examining the effectiveness of nurse education to improve venous thromboembolism prevention in hospitalized patients randomly assigned 21 floors within a hospital to one of two educational interventions 31. The benefits of cluster randomization may include the ability to study interventions that cannot be given to only selected patients (such as nurse education), and the ability to prevent contamination between individuals (ie, all nurses working together on the same floor receive the same intervention).…”
Section: Methodsmentioning
confidence: 99%
“…Cluster randomized trials might randomize at the floor, unit, clinic, or hospital level. For example, a cluster randomized trial examining the effectiveness of nurse education to improve venous thromboembolism prevention in hospitalized patients randomly assigned 21 floors within a hospital to one of two educational interventions 31. The benefits of cluster randomization may include the ability to study interventions that cannot be given to only selected patients (such as nurse education), and the ability to prevent contamination between individuals (ie, all nurses working together on the same floor receive the same intervention).…”
Section: Methodsmentioning
confidence: 99%
“…In one report, the compliance rate of patients with guidance from nurses was 85%, while the compliance rate of patients without guidance was 55%. 24 Therefore, all medical staff need to fully understand why a patient needs to wear a portable IPCD for VTE prophylaxis. By doing so, all medical staff can provide proper guidance to patients regarding the wearing method of the portable IPCD, which might consequently improve compliance with VTE prophylaxis and thus reduce the incidence of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, VTE affects 350,000 to 600,000 individuals every year and more than 100,000 individuals die annually. [4] Previous studies considered VTE as a rare disease in Asia. [5,6] However, many recent studies found that the incidence of VTE was not as low as previously thought, on the contrary, incidence of VTE may be increasing in recent years.…”
Section: Discussionmentioning
confidence: 99%